ENVIRONMENTAL INFORMATION DISCLOSURE AND FIRM VALUE OF LISTED MANUFACTURING COMPANIES IN NIGERIA - M.L. SUBAIR; N.O. SALAU; O.A. OYENIYI; B.B. ANIFOWOSE (Malete Journal of Accounting and Finance)
In recent times, firms’ neglect of their environmental and social responsibilities has become a matter of concern. Their activities are often aimed at making profit in line with the identified problem. The study examined environmental information disclosure and firm value of listed manufacturing companies in the Nigerian Stock Exchange Group (NSE). From a population of 56 listed manufacturing firms, a sample size of forty-eight (48) manufacturing firms was determined based on companies with complete information for all six (6) financial years studied. Random sampling technique was used to select amongst the secondary data which was sourced for from the audited annual financial reports of the sampled companies for the period of 2014 to 2019. The result of the study revealed that disclosures of emission and waste disclosure exhibit positive and significant impact on firm value; disclosures of biodiversity exhibits inverse and significant impact on firm value; and disclosures of compliance to environmental laws exhibits inverse significant impact on firm value at 5% error term. Based on the result, the study concludes that compliance with environmental laws and emissions disclosures